Pengaruh Model Pembelajaran Kooperatif Jigsaw terhadap Hasil Belajar Siswa Kelas XI Geografi SMA Negeri 1 Ampek Nagari - Dani, Santia Rahma; Mariya, Sri (YASIN, 2025)
Student learning outcomes in Geography at SMA Negeri 1 Ampek Nagari remain relatively low, partly due to the use of conventional, teacher-centered instructional methods that are monotonous and provide limited opportunities for critical thinking and deeper understanding of the material. This study aims to analyze the effect of the Jigsaw cooperative learning model on student learning outcomes in Geography. The research employed a quantitative experimental method with a Quasi-Experimental Non-Equivalent Control Group Design. The sample consisted of two classes an experimental class and a control class, each comprising 33 students selected through total sampling. Data were collected using tests, observation, and documentation, and analyzed through descriptive and inferential statistics, including normality, homogeneity, and hypothesis testing using paired-sample t-tests and independent-sample t-tests in SPSS. The results show a significant improvement in the experimental class, with mean scores increasing from 50.30 (pre-test) to 74.85 (post-test), compared to the control class, which improved from 51.06 to 63.94. The paired-sample t-test yielded p < 0.001, indicating a significant effect of the Jigsaw model on student learning outcomes. The study concludes that the Jigsaw cooperative learning model has a positive and significant impact on the Geography learning outcomes of Grade XI students at SMA Negeri 1 Ampek Nagari.